Home truths - Bellamy, Craig N.; Marshall, Matt, 1966- (Melbourne, Victoria : Penguin Group Australia, 2013)
Craig Bellamy is no ordinary coach. He has a remarkable win-loss record in his ten years with Melbourne Storm, but when he led his team through a season of scandal and turmoil, winning games while playing for no points, he gained national respect. For the first time, the legendary coach reveals his thoughts on subjects such as leadership, management, character, adversity, courage, teamwork, success and failure, by sharing his personal experiences. Known as a straight shooter and a man of great integrity, Bellamy knows how to bring out the best in people - he has created an enviable club culture. He's fair, generous, candid about his own shortcomings, and persuasive in his opinions about how best to achieve your goals and be successful. His philosophies rest on the pillars of humility, loyalty and discipline - values that stand the test of time. Anyone who works in a team or who wants to get the most out of themselves will benefit from this inspirational book - it's about making your own game plan for life.
"Michael Joseph an imprint of Penguin Books"
Imprint: e-penguin.
Print version record
Keywords: Bellamy, Craig N; Bellamy, Craig, -- 1979-; Bellamy, Craig, -- 1979-; Melbourne Storm (Football team); Failure (Psychology); Leadership; Rugby football coaches -- Australia -- Biography; Rugby football players -- Australia -- Biography; Rugby football players -- Australia; Self-actualization (Psychology); Success; Autobiography: sport; Failure (Psychology); Leadership; Self-actualization (Psychology); Success; Australian; Electronic books; Biographies